MORPHOMETRIC PARAMETERS RIVER BASIN APPLIED TO UNA (PERNAMBUCO-BRAZIL) SUSCEPTIBILITY TO IDENTIFY THE FLOODS - de-Araujo-Monteiro, Kleython; Magalhães-de-Barros, Ana Clara; Tavares-de-Melo, Rhaissa Francisca; Meira-Coelho-Ramos, Débora Albuquerque; Silva-Nóbrega, Ranyére; Girão, Osvaldo (Revista Geográfica de América Central., 2014)
This research applied morphometric parameters to the Una River Basin in the state of Pernambuco, Brazil, with the goal of determining if this watershed is susceptible to floods. In June of 2010 there was a catastrophic flooding event that devastated the city of Palmares. The application of this methods verified that this watershed isn’t susceptible to flooding, and this particular flood was a rare and anomalous event.